Pengaruh Pendapatan Perkapita Terhadap Konsumsi Rumah Tangga Perkapita di Provinsi Sulawesi Utara - Silalahi, Rosi Dearni; Laoh, Olly Esry Harryani; Sondakh, Mex Frans Lodwyk (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2025)
Per capita household consumption is an important indicator for assessing community welfare because it reflects the ability to meet basic needs. The higher the per capita consumption, the greater the purchasing power of the community, which indicates economic growth and improved quality of life. This consumption is closely related to per capita income, where an increase in income is believed to drive consumption. This study analyzes the impact of per capita income on per capita household consumption in North Sulawesi Province using secondary data from the Central Statistics Agency (BPS) from 2015 to 2024. The method used is simple linear regression with a quantitative approach, conducted from April to July 2025. The results of the study show a positive and significant relationship between per capita income and per capita household consumption. This means that the higher the income, the greater the household consumption. However, even without income, households still have basic consumption for essential needs. Overall, this research model is able to explain the relationship between the two variables with a high degree of accuracy, so the results can be trusted as a true reflection of the conditions on the ground.